Sikap dan Pandangan Civitas Akademik Keagamaan Terhadap Fatwa Majelis Ulama Indonesia (MUI) - Ilyas Umar; Ardi Ardi (Universitas Muslim Indonesia, 2022)
The social dynamics that have occurred in the last two years of this pandemic have opened up more space to ask how far the MUI fatwa has influenced the socio-religious behavior of the Muslim community. This research will then use a descriptive approach through surveys and a sociological approach to religion to try to describe, understand, and explain the attitudes and views of the religious academic community in Makassar against the MUI fatwa. The results of this study indicate that respondents in general (84%) acknowledge the credibility of the MUI in issuing fatwas and its relevance (77.8%) to religious teachings, needs, and developments of the times. In general, (73%) respondents think that MUI has been able to socialize its fatwa well. However, there is a note that some respondents were aware of several MUI fatwas through the controversy created by the fatwas themselves. There are inconsistencies that occur regarding the legal strength of the MUI fatwa and the right of the Muslim community to follow or not follow certain fatwas. The inconsistency arises because there are 71% of respondents who agree that the Muslim community has the right to follow or not follow a fatwa. However, 80% of respondents also agree that the MUI fatwa is binding on Muslims, and even 40% of them consider it obligatory to follow the MUI fatwa.